2017
DOI: 10.21608/alexja.2017.23206
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of combining ability and superiority percentage of half diallel crosses between yellow maize inbred lines for growth characters and some diseases resistance

Abstract: Half diallel cross among ten yellow maize inbred lines was made at Sakha Agriculture Research Station during the growing season 2015. The resultant 45 crosses along with two commercial hybrids as yellow checks (single crosses 162 and 168) were evaluated at two field experiments in two years 2016 and 2017. The results indicated that, years (Y) mean squares had significant effects for all traits, except resistance to downy mildew disease. Genotypes (G) and crosses (Cr) mean squares had high significant effects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This finding is agreement with those of, Turgut et al (1995); Amer et al (2002) and Mosa et al (2017) who reported the preponderance of non-additive gene effects in controlling the inheritance of downy mildew and grain yield. Whereas, El-Shenawy and Mosa (2005); Mosa et al (2009) and El-Refaey et al (2018) who found that grain yield and downy mildew resistance were mainly controlled by additive gene effects Table 7. Estimates of additive gene effects (K 2 GCA) and non-additive gene effects (K 2 SCA) for six traits and downy mildew resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is agreement with those of, Turgut et al (1995); Amer et al (2002) and Mosa et al (2017) who reported the preponderance of non-additive gene effects in controlling the inheritance of downy mildew and grain yield. Whereas, El-Shenawy and Mosa (2005); Mosa et al (2009) and El-Refaey et al (2018) who found that grain yield and downy mildew resistance were mainly controlled by additive gene effects Table 7. Estimates of additive gene effects (K 2 GCA) and non-additive gene effects (K 2 SCA) for six traits and downy mildew resistance.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of DM strains have been reported, and the resistance to them is polygenically controlled. El-Shenawy and Mosa (2005), Mosa et al (2009) and El-Refaey et al (2018) reported that additive gene effects played a major role in the expression of the inheritance of downy mildew disease. While, Turgut et al (1995), Amer et al (2002) and Mosa et al (2017) stated that non-additive gene effects played an effective role in the inheritance of downy mildew resistance.…”
Section: Introductionmentioning
confidence: 99%